Problematizing quantification of indirect land-use change (ILUC) Connected to expanding ethanol production in Brazil - Bryngelsson, David; Åhlén, Anders (My University, 2009)
Indirect land-use change is an important factor for the climatic performance of biofuels and has been the reason for a vivid debate, triggered by some attempts for quantification of the former, in 2008. In this study we evaluate the possibilities for quantification of indirect land-use change by using partial equilibrium models and compare this with the alternative approach offered by the emerging field of agent-based modeling. The investigation was performed in separate modules covering a methodology study on partial equilibrium models; a literature study on agent-based models; a qualitative description of land-use dynamics in Brazil; a description of an agent-based model, constructed as a part of the project; and a discussion on the potential for these types of models for explaining and quantifying indirect land-use effects. The partial equilibrium models are sensitive to choices made by the modelers and different research teams reach contradictory conclusions using similar methods; it is hard to trust any quantitative results regarding indirect effects based on subjective assumptions. The agent-based models are good tools for studying and understanding micro-level dynamics important for indirect-land use change, but seem too data intensive and complex to be used for quantification of indirect land-use change. Our conclusions suggest a hybrid model, using a combination of agentbased models for micro-dynamics and a partial equilibrium model for macrodynamics. This model would be a powerful tool for understanding causeeffect relationships and for improving the qualitative understanding of the system, but would probably still not be able to provide quantitative results. We propose that the question has been posed in the wrong way and that quantification of such complex effects cannot be done unequivocally, however, an understanding of the dynamics is fundamental for decision-makers and research should thus be continued.
Keywords: Energi; Transport; Hållbar utveckling; Miljöteknik; Teknik och social förändring; Energy; Transport; Sustainable Development; Environmental engineering; Technology and social change